THE STUDY OF DIAGNOSTIC POTENTIAL OF MONOCLONAL ANTIBODIES SPECIFIC TO THE MEMBRANE PROTEIN OF CHOLERA AGENT IN ENZYME-LINKED IMMUNOASSAY - V. V. Evdokimova; L. P. Alekseeva; V. P. Zyuzina; O. F. Kretenchuk; M. E. Yagovkin (Проблемы особо опасных инфекций, 2017)
Objective of the study was to develop peroxidase conjugate on the base of monoclonal antibodies (MCA) H2F6 and to study the possibility of its application for the detection of tcp+ Vibrio cholerae O1/O139 strains using direct ELISA methods.Materials and methods. Utilized for the investigation was the hybrid H2F6 clone, which synthesized monoclonal antibodies specific to the outer membrane protein of cholera vibrio into culture medium.Results and conclusions. Peroxidase conjugate was designed on the base of MCA which allows for the detection of tcp+ V. cholerae O1 and O139 strains in direct solid-phase enzyme-linked immunosorbent assay and dot-ELISA. The preparation was tested on a group of strains of V. cholerae and heterologous microorganisms and showed specificity in relation to V. cholerae O1 and O139. Monoclonal peroxidase conjugate H2F6 can be used for the detection of epidemically significant V. cholerae O1/O139 strains by means of immune-enzyme methods.